2008
DOI: 10.1120/jacmp.v9i1.2318
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment and characterization of a dual‐tube kilovoltage X‐ray localization system in the radiotherapy treatment room

Abstract: Although flat‐panel kilovoltage X‐ray imaging devices have been well tested for clinical use in diagnostic radiology, their use as a part of an image‐guided radiation therapy (IGRT) system in a treatment room is new and requires systematic assessment.We used the Novalis IGRT system (BrainLAB, Feldkirchen, Germany) for the present study. The system consists of two floor‐mounted kilovoltage X‐ray tubes projecting obliquely onto two flat‐panel detectors mounted on the ceiling. The system can automatically fuse tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
(20 reference statements)
2
15
0
Order By: Relevance
“…The image quality and quality assurance programs for the OBI (planar and CBCT) have been detailed in the studies by Yoo et al (70) and Bissonnette et al (71,72) Hyer et al (73) compared the qualities of two volumetric CBCT imaging systems, as well as the organ doses. Lee et al (74) assessed the image quality of the ETX system. Table 1 lists the technical specifications of the imaging detectors mounted on the NTX.…”
Section: B Imaging Tests B1 Image Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The image quality and quality assurance programs for the OBI (planar and CBCT) have been detailed in the studies by Yoo et al (70) and Bissonnette et al (71,72) Hyer et al (73) compared the qualities of two volumetric CBCT imaging systems, as well as the organ doses. Lee et al (74) assessed the image quality of the ETX system. Table 1 lists the technical specifications of the imaging detectors mounted on the NTX.…”
Section: B Imaging Tests B1 Image Qualitymentioning
confidence: 99%
“…The phantom contains 21 groups of line pairs with spatial frequencies ranging from 0.5 to 5.0 lp/mm. The spatial resolution can be quantified by visually determining the resolvable line pairs, or by plotting a relative modulation transfer function (RMTF) for more quantitative analysis, (74)(75)(76) as shown in Figure 1 Figure 1(c) shows an MV portal image of an aluminum phantom, known as the "Las Vegas" phantom (Varian Medical Systems, Palo Alto, CA), which contains circular discs of different sizes and thicknesses. The visible circles are marked qualitatively.…”
Section: B Imaging Tests B1 Image Qualitymentioning
confidence: 99%
“…1. (See Chen et al 18 or Lee et al 21 for a description of the kilovolt x-ray system). As the x-ray system is nonorthogonal, it is possible that the spatial accuracy is reduced along the axis that bisects the kV beam axes.…”
Section: Iic Determining the Accuracy Of Exactrac Coordinatesmentioning
confidence: 99%
“…The Novalis system consists of two X-ray tubes and digital imaging plates that provide 3D coordinates of the target. System characterization and clinical applications have been reported [59][60][61][62][63][64][65][66][67]. In a comparative study between ultrasound localization of the prostate and radiographic 3D imaging of radio-opaque markers, Fuller et al [68] found significant differences between the two methods.…”
Section: Brainlab Novalismentioning
confidence: 96%